Low Pulmonary Function in Individuals with Impaired Fasting Glucose: The 2007-2009 Korea National Health and Nutrition Examination Survey - Lee, Yun Jeong (Public Library of Science, 2013)
OBJECTIVE: To investigate the association between fasting plasma glucose level and pulmonary function. RESEARCH DESIGN AND METHODS: Nutritional information, pulmonary function data, and laboratory test data from 9,223 subjects from the fourth Korea National Health and Nutrition Examination Survey were examined. The participants were divided into five groups according to fasting plasma glucose (FPG) level: normal fasting glucose (NFG)1, FPG <90 mg/dl; NFG2, FPG 90-99 mg/dl; impaired fasting glucose (IFG)1: FPG 100-109 mg/dl; IFG2, FPG 110-125 mg/dl; and diabetes, FPG ≥126 mg/dl and/or current anti-diabetes medications. RESULTS: After adjustment for several variables, the percentage of predicted forced vital capacity(FVC%) decreased with increasing fasting plasma glucose level in both sexes[men: (mean ± SEM) 92.0±0.3 in NFG1; 91.9±0.3 in NFG2; 92.0±0.4 in IFG1; 90.2±0.7 in IFG2; and 89.9±0.5 in diabetes, P = 0.004; women: 93.7±0.3 in NFG1; 93.7±0.3 in NFG2; 93.1±0.5 in IFG1; 91.1±0.9 in IFG2; and 90.7±0.6 in diabetes, P<0.001]. A logistic regression analysis found that IFG2 and diabetes were independently associated with the lowest quintile of predicted FVC% (IFG2: odds ratio [95%CI], 1.50 [1.18-1.89], P = 0.001; diabetes: 1.56 [1.30-1.88], P<0.001) using NFG1 as a control. CONCLUSIONS: The current data suggest that forced vital capacity may begin to decrease in the higher range of IFG.